MEMPROGRAMKAN PENGENALAN AKUNTANSI SYARIAH BAGI USAHA MIKRO KECIL DAN MENENGAH DESA CIBITUNG TENGAH, KECAMATAN TENJOLAYA, BOGOR - Tubagus Rifqy Thantawi; Destriana Maulani; Yal Robiansyah (Jurnal Pengabdian Kepada Masyarakat Perbankan Syariah: Program Studi Perbankan Syariah., 2022)
This community service aims to minimize financial recording errors. The subjects of thiscommunity service are the people of Central Cibitung Village, Tenjolaya District, Bogor Regency,West Java Province. In this community service, activities are carried out based on futureprospective methods (things that may happen in the future) through community service activities.The results of this activity indicate that MSME actors in Central Cibitung Village in running theirbusiness tend not to practice sharia accounting. There are also some MSME actors in CentralCibitung Village who do not understand accounting and what the purpose of making financialreports is. This community service activity helps provide advice, motivation and knowledge to allMSME actors in Central Cibitung Village to apply simple accounting practices in their businessactivities so that they can improve their business financial performance.